Local levels of lymphocytes and cytokines in colon cancer patients with bowel obstruction - N. I. Simonenko; E. Yu. Zlatnik; E. A. Dzhenkova; O. G. Shulgina; E. S. Bondarenko; A. Yu. Maksimov; A. A. Maslov; A. V. Snezhko (Южно-Российский онкологический журнал)
Purpose of the study. To study local immunity and cytokine levels in colon cancer patients with subcompensated intestinal obstruction.Patients and methods. In 60 patients with locally advanced left-side colon carcinoma (30 with and 30 without bowel obstruction) during the surgery samples of tumor, peritumoral area and resection line tissue were obtained. After disintegration of tissue samples Т-, В-, NK-lymphocytes` subsets (CD3+, CD4+, CD8+, CD4+CD25+CD127dim, CD19+, CD16+CD56+) were studied by flow cytometry and inflammatory cytokines` content (TNF-α, IL-1α, IL-6, IL-8) via ELISA test.Results. Higher levels of interleukins were shown in the tumors of patients in both groups compared to the tumor-free tissue samples. In the presence of subcompensated intestinal obstruction, local levels of proinflammatory cytokines were higher than in patients who did not have it: IL-6 and IL-1a in all tissues studied, IL-8 in tumor and peritumoral zone samples; TNF-α – in the tumor and the resection line. In the absence of intestinal obstruction in the tumor tissue, compared with non-tumor samples, the content of T-lymphocytes was increased due to CD4+ and CD8+, and Tregs levels were lower. These differences were leveled in the presence of intestinal obstruction, i.e. accumulation of T-lymphocytes in the tumor, providing adaptive immunity, was not observed in such patients. Their lower levels of CD8+ T cells and higher levels of Tregs in the tissue of the resection line form a low cytotoxic potential of the tissue remaining after surgery.Conclusions. The presence of subcompensated intestinal obstruction in patients with colon cancer leads to a number of quantitative changes in local immunity factors compared with patients in whom it was not detected or was compensated. Among these changes, a particularly unfavorable content of pro-inflammatory cytokines, in particular IL-6, in the tissue of the resection line, along with a lower number of CD8+ T lymphocytes and a higher number of Tregs, which suggests a decrease in antiproliferative potential not only in the tumor, but also in non-tumor tissues.